Durability and microstructure aspects of sustainable concrete made with ceramic waste: a review - Ahmad, Jawad; Sabri, Mohanad Muayad; Majdi, Ali; Alattyih, Wael; Khan, Inamullah; Alam, Muhammad (Frontiers in Materials, 2025)
The construction industry consumes natural resources rapidly due to the increased population which requires the development of modern buildings. Therefore, several researchers pay attention to promoting sustainable construction. Among different types of waste, ceramic waste (CW) gained attention in concrete production which reduced the waste dumps from the ceramic industry and improved concrete sustainability. Although several researchers recommend the suitability of CW in concrete production. However, a detailed review is required which summarizes all the relevant information and provides compressive information on its impact on concrete performance. Recently, different researchers reviewed the suitability of CW in concrete. However, most researchers focus on strength properties while limited researchers focus on the durability and microstructure properties of CM concrete. Therefore, this review summarized the concrete durability and microstructure aspects with the substitution of CW. The durability performance of concrete was evaluated through percentages of voids, chloride penetration, water absorption, sulfuric acid resistance, shrinkage, freeze and thaw effect, corrosion resistance, and sulfate resistance. Furthermore, microstructure was reviewed through x ray diffraction, thermal stability, pozzolanic activity and scanning electronic microstructure. Also, the review evaluates the environmental and cost-benefits analysis of CW concrete through embodied energy (EE), carbon emissions (ECO2e), and costs. The findings indicate that CW can effectively replace 10%–15% of conventional materials in concrete, offering both environmental and economic advantages.